PERSEPSI ORANG TUA ETNIS MADURA TENTANG PENDIDIKAN ANAK DI RT 03 RW 07 SEPAKAT 2 KELURAHAN BANSIR LAUT - Saputri, Urai Tiara; Budjang, Gusti; Parijo, Parijo (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the perceptions of Madurese Ethnic parents in RT 03 RW 07 about the educational needs and interests of children. The research method used is descriptive with a form of qualitative research. Data collection techniques used were interview, observation, and documentation study. The data collection tools were observation guides, interview guides and documentation. The analysis in this study was presented in a descriptive qualitative manner using 7 informants from 48 households in RT 03 RW 07. The informants consisted of 1 RT 03 RW 07, and 6 other ethnic Madurese parents who were residents in RT 03 RW 07. The basis for determining the informant is a recommendation from the Head of RT 03 RW 07. The results of this study indicate that Madurese Ethnic parents in RT 03 RW 07 assume that education for children is important. Seen how Madurese ethnic parents try to support children's education by meeting the educational needs of children and trying to foster children's educational interests.Â Keywords: Parents' Perception, Madurese Ethnic, Children's EducationÂ